O ADOLESCENTE E A TELEVISÃO REGIONAL: estudo da audiência do programa Em Movimento - Silva, Carla Pollake da (2004)
This is an audience study focusing on a regional TV show called "Em Movimento". The show is locally produced and broadcast by TV Gazeta, a TV Globo affiliate. It aims at reaching the young audience (teenagers). The study objective is to bring out the motivations that drive the young audience to watch this show and the gratifications they derive from it. The research project is based on both the regional concepts and the uses and gratification perspective. The data were collected through focus groups of youngters in the age bracket of 15 to 18 years old. It is ended that the adolescents have as main motivations to attend the Em Movimento the will of learning on itself and on the atmosphere in that you/they live, to confirm concepts already established by them same and still if they feel close to the reality portrayed in the program.